DAMPAK KURIKULUM PENDIDIKAN AGAMA KRISTEN DAN METODE MENGAJAR TERHADAP PEMBENTUKAN KARAKTER SISWA - Purim Marbun; Shirley Lasut; Penni Ani Simanungkalit (Edukasi : Jurnal Pendidikan Agama Kristen, 2023)
Character education has become a crucial issue in the context of modern education, where schools are expected not only to produce intellectually competent graduates but also individuals with strong character. This study aims to analyze the impact of the Christian Religious Education (CRE) curriculum and teaching methods on character formation among students in Christian secondary schools. The research employed a qualitative approach with a case study design. The research subjects were CRE teachers and students selected purposively, while data were collected through interviews, observations, and document analysis. Data were analyzed using Miles and Huberman’s model with source triangulation techniques to ensure validity. The findings indicate that the CRE curriculum has a significant influence on the development of students’ moral, spiritual, and social character. Participatory, contextual, and project-based teaching methods proved to be more effective in internalizing character values compared to lecture-based methods. The synergy between curriculum and teaching methods serves as a key factor in realizing transformative character education, enabling students not only to understand Christian values conceptually but also to embody them in daily life. The study recommends strengthening school policies, enhancing teacher competencies, and providing supportive facilities to ensure that character education based on CRE can be implemented more optimally and sustainably.